Overcoming the myths of esketamine administration: different and not difficult - Buchmayer, Florian; Kasper, Siegfried (Frontiers in Psychiatry, 2023)
Intranasal esketamine for treatment-resistant depression has been introduced and approved by the FDA and EMA in 2019 and 2020, respectively. Since then, the administration practices were found different among countries. Major depression has a high impact on many humans lives worldwide and more than a third of treated people are not responding after several treatment attempts. Additional administration with esketamine closed this gap for more than the half of these non-responders. Guidelines for the treatment of major depression recommend starting with add-on esketamine after 2-4 serious attempts of treatment with a standard antidepressants (SSRI/SNRI) irrespective of augmentation with others, eg. second generation antipsychotics or lithium. Thus, intranasal esketamine became an important role in the evidence-based treatment of major depression. The authors review and critically evaluated published articles focusing on preparation, management and observation of intranasal esketamine treatment. There exists a clear recommendation for administrating intranasal esketamine in a medical environment, not limited to a clinical setting for selecting the dose, monitoring the improvements and managing adverse events. The administration of intranasal esketamine is considered as safe during the application itself and long-lasting or severe adverse events during long-term treatment are very rare. Since this is a new approach for treatment application psychiatrists face new different but not difficult treatment procedures compared to prescribing only a medication.